Tantangan Pondok Pesantren dalam Menghadapi Era Bonus Demografi - Ibnu Chudzaifah (Al-Riwayah : Jurnal Kependidikan, 2018)
Pondok Pesantren is one of the Islamic educational institutions that aim to form human beings who have noble character, so that created a human who has a balance between physical and spiritual. Some educational institutions offer various models of learning to balance the current development so that its existence is still recognized by the community. While boarding school in dealing with the development of the times, has a commitment to make new innovations by presenting the pattern of education that can give birth to a reliable Human Resources. Especially pesantren currently has a challenging enough weight in facing the era of "Demographic Bonus". Demographic bonus is a phenomenon in which the structure of the population greatly benefits the community from the side of development in various sectors, because the productive age is more than the non productive age. This means that the dependency burden will decrease with the ratio of 64 percent of the productive age population to bear only 34 percent of the nonproductive age population. With all kinds of scholarships and skills given to students, students are expected to compete in all fields, especially in the face of Indonesia gold in 2020 to 2035